Obesity and asthma: risk, control and treatment - Marko, Monika; Pawliczak, Rafał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Asthma and obesity are currently one of the most common diseases. Observing an increase in morbidity of obesity and asthma, it can be concluded that there is a link between these diseases. But the mechanism of this relation is not well known. Due to reduced movement in patients and treatment, asthma is conducive to obesity, and obesity can exacerbate the symptoms associated with asthma. Obesity can affect bronchial hyperresponsiveness. Increasing body fat in obese people leads to systemic inflammation and elevated serum levels of many proinflammatory cytokines (e.g. leptin) and anti-inflammatory ones (e.g. adiponectin) that can have a causal relationship to bronchial asthma, but human studies are ambiguous. Obese asthmatics are characterized by a phenotype: heavier asthma, worse response to treatment and control of asthma. It has been found that in obese people, weight loss reduces the severity of asthma symptoms, so in these patients, treatment should include weight control.